1997
DOI: 10.1177/135676679700300402
|View full text |Cite
|
Sign up to set email alerts
|

Travel decision pattern segmentation of pleasure travel

Abstract: The purpose of this research is to identify the different types of travel decisiorr patterns iii the japanese travel market. In contrast to previous studies, a multi-stage segmentation base (travel philosophy — travel benefit sought - travel product preference) ivas used to identify six decision groups of Japanese travellers. The results showed that travel decision pattern segmentation is a viable segmentation approach. Implications of the findings are discussed for this important area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Activity-based segmentation can be used together with other psychographic, demographic and/or social variables in order to effectively segment, define and differentiate the target market. Different factor structures were encountered in activity-based market segmentation, implemented in different periods and in different geographies (Choi et al, 2011; Choi and Tsang, 2000; Hsieh et al 1997; Lehto et al 2004; Morrison et al, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Activity-based segmentation can be used together with other psychographic, demographic and/or social variables in order to effectively segment, define and differentiate the target market. Different factor structures were encountered in activity-based market segmentation, implemented in different periods and in different geographies (Choi et al, 2011; Choi and Tsang, 2000; Hsieh et al 1997; Lehto et al 2004; Morrison et al, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A large number of tourist typologies is described in professional literature (e.g. Cohen, 1972Cohen, , 1979Hsieh et al, 1997;Decrop & Snelders, 2005).…”
Section: Theoretical Basismentioning
confidence: 99%
“…Similarly, Lehto et al (2004) classified groups of travelers themed around nature appreciation, culture, shopping, tours, contrived entertainment, outdoor recreation, and sports. Hsieh et al (1997) identified six interrelated groups of travelers that participated in different combinations of similar activities. He even classified some travelers as general tourists because they pursued too many different types of activities so they did not fit into any of the other specialized categories.…”
Section: Cluster Analysis-based Studiesmentioning
confidence: 99%
“…Further, the descriptive analysis studies focus on broad main trip purposes, which describe the long-distance activity component of travel described above (see, for example, Gitelson and Kerstetter, 1990;Hsieh et al, 1997;Hwang and Fesenmaier, 2003;Hackney, 2004;Kemperman et al, 2006;Erhardt et al, 2007). Not surprisingly, there is even disagreement on how these broad main trip purposes should be defined to best describe the combinations of activities individuals pursue during a trip (e.g.…”
Section: Descriptive Analysis-based Studiesmentioning
confidence: 99%